Performance evaluation of magic square based spatial modulation in UAV communication - Tastan, Mustafa Cihan; Ilhan, Haci (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study proposes a method to reduce the bit error rate (BER) in communications by unmanned aerial vehicles (UAVs). The method involves using specific active antennas that transmit at precise times with a particular mapping, ensuring orthogonality among transmitting antennas. This technique can accommodate numerous transmit antennas and amplitude-phase modulation orders. When applied to spatial modulation (SM) and generalized spatial modulation (GSM), it demonstrates clear superiority and significantly improved results compared to traditional SM and GSM methods, especially at high altitudes where conventional methods result in high BER. Introducing a new modulation method called magic square (MS) further enhances the results. The MS method provides a unique orthogonality pattern for the transmitting antenna sets. Additionally, the study introduces the utilization of magic squares in the modulation field. The MS-based SM model shows a BER rate almost 103 times lower than traditional SM at the 25 dB signal-to-noise ratio (SNR) level for various fly altitudes. Similarly, the MS-based GSM model demonstrates a BER rate almost 100 times lower than traditional GSM. The proposed method yields better results as the altitude increases, making it suitable for UAV communication at various altitudes.
Keywords: Air-to-air (A2A); Air-to-ground (A2G); Generalized spatial modulation (GSM); Magic square (MS); Spatial modulation (SM); Unmanned aerial vehicle (UAV); UNMANNED AERIAL VEHICLES; CIVIL APPLICATIONS; MODEL; Automation & Control Systems; Engineering; Mathematics